Trends in Open and Arthroscopic Long Head of Biceps Tenodesis. Issue 1 (February 2020) - Saltzman, Bryan M.; Leroux, Timothy S.; Cotter, Eric J.; Basques, Bryce; Griffin, Justin; Frank, Rachel M.; Romeo, Anthony A.; Verma, Nikhil N.
Background: In young and active patients, long head of biceps (LHB) tenodesis has become a common procedure for managing LHB pathology, but it remains unclear whether it is performed in isolation or along with other shoulder procedures and whether open and arthroscopic techniques produce different complications. Questions/Purposes: We sought to determine and compare open and arthroscopic LHB tenodesis in terms of (a) trends in overall use, (b) trends in use in isolation and in association with rotator cuff repair (RCR) and superior labral tear from anterior-to-posterior (SLAP) debridement/repair, and (c) the rates of post-operative complications. Methods: We performed a retrospective analysis of data from an insurance database to identify LHB tenodesis procedures performed from 2011 to 2014. The overall annual rates of open and arthroscopic LHB tenodesis were determined and then stratified according to concurrent RCR and SLAP repair/debridement. A multivariate logistic regression analysis that controlled for patient demographics (age, sex, comorbidity) was performed. Results: Overall, 8547 patients underwent LHB tenodesis, of which 43.5% were open and 56.5% were arthroscopic procedures. There was a significant increase in the utilization of LHB tenodesis from 2011 to 2014. In isolation, open LHB tenodesis was the more common technique overall and by year. Arthroscopic LHB tenodesis was the most common tenodesis technique performed in conjunction with RCR and SLAP repair/debridement. The overall complication rate was 2.9%; only wound dehiscence demonstrated a difference between techniques. Conclusions: The rates of open and arthroscopic LHB tenodesis procedures increased significantly from 2011 to 2014, with open techniques more common when LHB tenodesis is performed in isolation and arthroscopic techniques more common when performed as a concomitant procedure. Our use of a population database did not allow us to evaluate biomechanical or cost-related phenomena, and future research should examine these and other relevant differences between these two LHB tenodesis techniques.